2023
DOI: 10.1186/s13256-023-03847-8
|View full text |Cite
|
Sign up to set email alerts
|

Idiosyncratic drug-induced liver injury related to use of novel selective androgen receptor modulator RAD140 (Testalone): a case report

Abstract: Background RAD140 (Testalone) is a novel selective androgen receptor modulator with very limited data currently available on adverse effects related to this compound. The first-in-human phase 1 trial was recently published and did report a significant proportion of elevated aspartate aminotransferase, alanine transaminase, and total bilirubin among the test subjects. RAD140 may be associated with an idiosyncratic drug-induced liver injury. It is easily purchased online as a workout supplement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…peak 73 IU/L); TB 0.8 mg/dL Negative No No medical history Not mentioned Arayangkool et al [ 46 ] LGD-4033 Ostarine RAD-140 Jaundice Pruritus Weight loss Abdominal pain Cholestatic liver injury Canalicular bile plugs Hepatocellular dropout Acute tubular injury with pigmented bile casts 8 weeks No AST 52 IU/L ALT 52 IU/L ALP 343 IU/L TB 43.3 mg/dL Negative No No medical history Analytical testing for SARMS not performed. Dose was not specified Reported biopsy Ladna et al [ 47 ] RAD-140 Nausea, vomiting, severe right upper quadrant abdominal pain, jaundice, dark urine, constipation Acute liver injury 8 weeks No AST 51 IU/L ALT 243 IU/L TB 4.9 mg/dL Negative No No medical history Analytical testing for SARMS not performed Mohamed et al [ 48 ] RAD-140 Jaundice, nausea, fatigue, dark urine, acholic light gray-colored stool, pruritus Mixed portal hepatitis, cholestasis, biliary reactive changes 16 weeks Performance-enhancing supplement AST 70.8 IU/L (1.18 µkat/L) ALT 99.6 IU/L (1.66 µkat/L) ALP 318 IU/L (5.3 µkat/L) TB 427.5 mg/dL Negative No No medical history Analytical testing for SARMS not performed. Dose was not specified Reported biopsy Cardaci et al [ 49 ] LGD-4033 10 mg daily Controlled study—not reported Controlled study—not reported 5 weeks …”
Section: Resultsmentioning
confidence: 99%
“…peak 73 IU/L); TB 0.8 mg/dL Negative No No medical history Not mentioned Arayangkool et al [ 46 ] LGD-4033 Ostarine RAD-140 Jaundice Pruritus Weight loss Abdominal pain Cholestatic liver injury Canalicular bile plugs Hepatocellular dropout Acute tubular injury with pigmented bile casts 8 weeks No AST 52 IU/L ALT 52 IU/L ALP 343 IU/L TB 43.3 mg/dL Negative No No medical history Analytical testing for SARMS not performed. Dose was not specified Reported biopsy Ladna et al [ 47 ] RAD-140 Nausea, vomiting, severe right upper quadrant abdominal pain, jaundice, dark urine, constipation Acute liver injury 8 weeks No AST 51 IU/L ALT 243 IU/L TB 4.9 mg/dL Negative No No medical history Analytical testing for SARMS not performed Mohamed et al [ 48 ] RAD-140 Jaundice, nausea, fatigue, dark urine, acholic light gray-colored stool, pruritus Mixed portal hepatitis, cholestasis, biliary reactive changes 16 weeks Performance-enhancing supplement AST 70.8 IU/L (1.18 µkat/L) ALT 99.6 IU/L (1.66 µkat/L) ALP 318 IU/L (5.3 µkat/L) TB 427.5 mg/dL Negative No No medical history Analytical testing for SARMS not performed. Dose was not specified Reported biopsy Cardaci et al [ 49 ] LGD-4033 10 mg daily Controlled study—not reported Controlled study—not reported 5 weeks …”
Section: Resultsmentioning
confidence: 99%